The Effectiveness of the Rabeg Application with the SP4N Lapor Application as A Public Service Innovation in the City of Serang - Isnaeni Wuri Lestari; Ipah Ema Jumiati; Florentina Ratih Wulandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research focuses on analyzing the effectiveness of integrating the Rabeg application with the SP4N Lapor application as a public service innovation in Serang City. The purpose of this study is to: is to find out how much the Effectiveness of the Integration of the Rabeg Application with the SP4N Lapor Application as a Public Service Innovation in Serang City. The theory of effectiveness uses Duncan's theory (Steers, 2012:53), including the achievement of goals, integration and adaptation. The research method uses a quantitative method. The sampling technique uses accidental sampling of 204 respondents. The results of the study show that the Effectiveness of the Integration of the Rabeg Application with the SP4N Lapor Application as a Public Service Innovation in Serang City is declared effective because it gets an assessment of more than 65% based on the hypothesis test criteria if the calculated tvalue is greater than the ttable (2.679 > 1.882), then H0 is rejected and Ha is accepted. The percentage of the Effectiveness of the Integration of the Rabeg Application with the SP4N Lapor Application as a Public Service Innovation in Serang City according to the responses of research respondents is 67%. Research suggestions include increasing socialization through the distribution of brochures, installing advertisements/banners and holding training related to the use of technology for OPDs integrated with the Rabeg Application and the SP4N Lapor Application.